Tribocorrosion resistance of CoCrFeNiNbx laser-clad coatings in the neutral and acid solutions. (February 2023) - Li, R.L.; Li, J.; Yan, Y.N.; Shao, M.; Li, J.
Abstract: In view of the poor tribocorrosion and corrosion resistance of Ti6Al4V, the coating of CoCrFeNiNb x ( x = 0, 1.0) was prepared on Ti6Al4V by laser cladding. The effects of Nb addition on the microstructure, mechanical and chemical performance were researched comprehensively. The tribocorrosion, and corrosion resistance of the coatings in the neutral (PH = 7) and acid (PH = 3) solutions were especially highlighted. The results showed that the three main phases of ɑ(Ti), Ti2 Ni and TiC were synthesized in the coatings. The more serious lattice distortion and the precipitation of a new phase (Cr2 Nb) resulting from the introduction of Nb caused the average microhardness increased from 621.0 HV0.2 to 666.6 HV0.2, which is greatly improved by 75.4 % (without Nb) and 88.2 % (with Nb) when compared with that of the substrate (354.1 HV0.2 ). The two coatings showed more excellent tribocorrosion than the substrate due to their average wear rate reduced by 66.9 % (neutral solution) and 90 % (acid solution). The introduction of Nb made the wear rate further decreased from 8.37 × 10 -4 A·cm 2 to 3.20 × 10 -4 A·cm 2 (neutral solution), and from 2.45 × 10 -4 A·cm 2 to 1.06 × 10 -4 A·cm 2 (acid solution). The coating with Nb also demonstrated more outstanding corrosion resistance than the coating without Nb and the substrate regarding to the corrosion potential and the corrosion current density in the two solutions. The addition of Nb contributed to the denser oxide film more rapidly formed on the surface of the coating. The poor tribocorrosion resistance of Ti6Al4V served in the neutral and acid solutions can be greatly improved by fabricating a CoCrFeNiNb on it.